A Quantitative Assessment of the Impact of Credit on Economic Growth in Russia - Victor, Byvshev; Natalya, Brovkina (Journal of Reviews on Global Economics, 2021)
The Russian credit market reflects the significant range of problems faced by the national economy. Among them are structural and regional imbalances; restrictions that prevent the free movement of funds in the interbank market; uncertainty that leads to a slowdown in the rates of attraction and placement of credit resources. As a result, the question arises as to how effective the credit market in Russia is and whether it has a stimulating effect on the national economy. The purpose of this article is to assess the impact of credit on economic growth as one of the criteria for the effectiveness of the credit market in the national economy. Growth rates of real quarterly GDP levels cleared of seasonality as well as quarterly growth rates of real household consumption in Russia cleared of seasonality are viewed as indicators of economic growth. Indicators of the credit market include quarterly growth rates of real loans to households and quarterly growth rates of real loans to non-financial organizations. In addition, such events as the global economic crisis of 2008 - 2009 and its impact, Western sanctions and the increase of crude oil prices were taken into account. As a result of the study conducted by the authors using an open econometric model of vector autoregression, the conclusion was drawn that loans to households and non-financial organizations in the long term have a stimulating effect on the Russian economy.